From Building a First-Generation Digital Library Infrastructure to Reimagining Discovery - Stuart Snydman; Martha Whitehead (International Journal of Digital Curation)
Twenty-five years ago, Harvard University was in the early stages of a project to build a first-generation digital library infrastructure. The project was carefully named the Library Digital Initiative (LDI), signifying that ‘digital’ would be an integral and integrated aspect of ‘library’ and not a separate entity. The initiative aimed to develop knowledge and expertise relating to digital objects, as well as technical infrastructure to create, curate, access and preserve them, and to integrate the new digital collections with Harvard’s extensive tangible collections.